Macrophage invasion contributes to degeneration of stria vascularis in Pendred syndrome mouse model - Jabba, Sairam V.; Oelke, Alisha; Singh, Ruchira; Maganti, Rajanikanth J.; Fleming, Sherry D.; Wall, Susan M.; Everett, Lorraine A.; Green, Eric D.; Wangemann, Antje Philine (My University, 2013)
Background: Pendred syndrome, an autosomal-recessive disorder characterized by deafness and goiter, is caused by a mutation of SLC26A4, which codes for the anion exchanger pendrin. We investigated the relationship between pendrin expression and deafness using mice that have (Slc26a4+/+ or Slc26a4+/-) or lack (Slc26a4-/-) a complete Slc26a4 gene. Previously, we reported that stria vascularis of adult Slc26a4-/- mice is hyperpigmented and that marginal cells appear disorganized. Here we determine the time course of hyperpigmentation and marginal cell disorganization, and test the hypothesis that inflammation contributes to this tissue degeneration. Methods: Slc26a4-/- and age-matched control (Slc26a4+/+ or Slc26a4+/-) mice were studied at four postnatal (P) developmental stages: before and after the age that marks the onset of hearing (P10 and P15, respectively), after weaning (P28-41) and adult (P74-170). Degeneration and hyperpigmentation stria vascularis was evaluated by confocal microscopy. Gene expression in stria vascularis was analyzed by microarray and quantitative RT-PCR. In addition, the expression of a select group of genes was quantified in spiral ligament, spleen and liver to evaluate whether expression changes seen in stria vascularis are specific for stria vascularis or systemic in nature. Results: Degeneration of stria vascularis defined as hyperpigmentation and marginal cells disorganization was not seen at P10 or P15, but occurred after weaning and was associated with staining for CD68, a marker for macrophages. Marginal cells in Slc26a4-/-, however, had a larger apical surface area at P10 and P15. No difference in the expression of Lyzs, C3 and Cd45 was found in stria vascularis of P15 Slc26a4+/- and Slc26a4-/- mice. However, differences in expression were found after weaning and in adult mice. No difference in the expression of markers for acute inflammation, including Il1a, Il6, Il12a, Nos2 and Nos3 were found at P15, after weaning or in adults. The expression of macrophage markers including Ptprc (= Cd45), Cd68, Cd83, Lyzs, Lgals3 (= Mac2 antigen), Msr2, Cathepsins B, S, and K (Ctsb, Ctss, Ctsk) and complement components C1r, C3 and C4 was significantly increased in stria vascularis of adult Slc26a4-/- mice compared to Slc26a4+/+ mice. Expression of macrophage markers Cd45 and Cd84 and complement components C1r and C3 was increased in stria vascularis but not in spiral ligament, liver or spleen of Slc26a4-/- compared to Slc26a4+/- mice. The expression of Lyzs was increased in stria vascularis and spiral ligament but not in liver or spleen. Conclusion: The data demonstrate that hyperpigmentation of stria vascularis and marginal cell reorganization in Slc26a4-/- mice occur after weaning, coinciding with an invasion of macrophages. The data suggest that macrophage invasion contributes to tissue degeneration in stria vascularis, and that macrophage invasion is restricted to stria vascularis and is not systemic in nature. The delayed onset of degeneration of stria vascularis suggests that a window of opportunity exists to restore/preserve hearing in mice and therefore possibly in humans suffering from Pendred syndrome.
Keywords: Pendred syndrome; Macrophage; Mice; Stria vascularis; Hyperpigmentation